1982
DOI: 10.1152/ajpgi.1982.242.4.g360
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli heat-stable toxin: its effect on motility of the small intestine

Abstract: Escherichia coli heat-stable enterotoxin is a low-molecular-weight substance that has been shown to induce the active secretion of fluid and electrolytes in the small intestine. In this study, we have characterized the effects of purified E. coli heat-stable toxin (ST, strain 18D, serotype 042:K86:H37) on the motility of rabbit small intestine by using myoelectric recording techniques. Substances, such as cholera toxin, that activate the adenylate cyclase-cAMP system induced predominantly migrating action-pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The intestine exhibits exaggerated secretomotor reflexes, causing diarrhea, when levels of bacteria and bacterial toxins in the gut lumen are excessive [184,185]. Bacteria and parasites in the gut lumen also trigger powerful propulsive reflexes that help to expel these organisms [186][187][188]. Vomiting, which involves retropulsive reflexes in the small intestine, is also used to eliminate undesirable contents from the gut.…”
Section: Enteric Nervous System Responses To Noxious Stimulimentioning
confidence: 99%
“…The intestine exhibits exaggerated secretomotor reflexes, causing diarrhea, when levels of bacteria and bacterial toxins in the gut lumen are excessive [184,185]. Bacteria and parasites in the gut lumen also trigger powerful propulsive reflexes that help to expel these organisms [186][187][188]. Vomiting, which involves retropulsive reflexes in the small intestine, is also used to eliminate undesirable contents from the gut.…”
Section: Enteric Nervous System Responses To Noxious Stimulimentioning
confidence: 99%
“…There is much evidence that endotoxins play a significant role in endotoxemic shock and gastrointestinal motility disturbances. 6,13,[15][16][17][18][19][20][21] According to a number of experimental studies, the first effects of endotoxin were seen after 60 min and it seems likely that these effects were indirect. 15,22 The symptoms were most severe 90-120 min after endotoxin injection, 22 and endotoxin produced profound disruption of normal fasting bowel motility patterns.…”
Section: Resultsmentioning
confidence: 99%
“…17 Motility disturbances resulting from endotoxemia are still a major concern, and prostaglandins have been increasingly implicated as significant pathophysiologic mediators in circulatory shock. 1,6,12,16,17,22 The effect of LTs is similar to many of the pathophysiologic sequelae of endotoxemia. Several studies have suggested that LTs may be significant pathogenic mediators in endotoxemia.…”
Section: Resultsmentioning
confidence: 99%
“…The secretomotor reflex pathways that are stimulated by cholera toxin pass through the myenteric plexus, and the reflex is prevented by ablating this plexus (Jodal et al, 1993). Defensive responses, such as the reverse peristalsis in the small intestine that occurs in vomiting, and exaggerated propulsive activity (Mathias et al, 1982;Vallance et al, 1997) and secretion (Lundgren, 2002) in the large intestine are mediated through the enteric nervous system and can be triggered by noxious chemicals or pathogens.…”
Section: Infectious Diarrheamentioning
confidence: 99%